Effects of Different Beverages on Color Stability of Bulk-Fill Restorative Materials - Esra Özyurt; Ayşegül Kurt (Ankara University, 2022)
Purpose: The aim of the study is to evaluate the color stability of a conventional composite resin and bulk-fill composite resins. Material Methods: A total of 120 samples of 10 mm diameter and 2 mm thickness were prepared from three bulk-fill (Beautifil Bulk-Fill, Filtek One Bulk-Fill, Tetric N-Ceram Bulk-Fill) and one conventional composite (Z250) and light cured. Initial color measurements were made with a spectrophotometer. Samples for each composite were randomly divided into 3 groups (black, kombucha and matcha tea) (n = 10). The samples were kept in the solutions for 12 days, and the color measurement was repeated. The values of ΔL, Δa, Δb and ΔE00 were calculated. SEM images were taken from a randomly selected sample from each group. Two-way analysis of variance (ANOVA) with Bonferroni correction was used to evaluate the color parameters. Results: Beautifil composite showed the greatest change in all values of E00, ΔL, Δa, and Δb., Filtek One and Tetric N-Ceram had the highest ΔE00 values values after Beautifil, respectively, and there was no difference between Z250 and Tetric N-Ceram. The lowest ΔL value belonged to Z250 composite, there was no difference between Tetric N-Ceram and Filtek One. Tetric N-Ceram had the highest Δa value after Beautifil and, there was no difference between the Z250 and Filtek One. Filtek One had the highest Δb value after Beautifil, there was no difference between the Tetric N-Ceram and Z250. Conclusion: Beverages can negatively affect the surface properties of bulk-fill composite resins in terms of color stability.